2018
DOI: 10.1016/j.ijdevneu.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Immature sleep pattern in newborn rats when dams encountered sleep restriction during pregnancy

Abstract: There is a growing realization that proper sleep during pregnancy is essential for the health of the mother and the offspring. However, there are no reports on the effects of maternal sleep restriction on the sleep-wake profiles of newborns. So, this study was conducted to evaluate the effects of sleep restriction during the third term of pregnancy on the sleep-wake profiles of neonates born to them. The female pregnant Wistar rats were sleep restricted for 5 h/day on gestational days 15-20 by gentle handling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
(106 reference statements)
0
17
0
Order By: Relevance
“…The feeding problem in the pup prior to weaning limits early sleep recording to only one or several hours a day. In the previous studies, formula milk was administered orally by syringe before sleep recording (2, 3, 17, 18, 20). The milk-feeding system used in our study was set up with a computer-assisted infusion pump and a conterminous PE tube connected to feeding catheter inserted into one side of oral cavity, and delivered milk once an hour (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feeding problem in the pup prior to weaning limits early sleep recording to only one or several hours a day. In the previous studies, formula milk was administered orally by syringe before sleep recording (2, 3, 17, 18, 20). The milk-feeding system used in our study was set up with a computer-assisted infusion pump and a conterminous PE tube connected to feeding catheter inserted into one side of oral cavity, and delivered milk once an hour (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the sleep-wake states in rat pups are identified by combining visual observation with measurements of muscle activity and EEG recordings (2, 1720). However, most of these studies observed and recorded intermittently, which means they cannot get 24 h continuous recordings, and cannot elaborated the dramatic changes and circadian development during the whole day in early life.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have not been consistent regarding the impact of circadian alterations and more data are needed to enable any robust conclusion. Gulia, 2018aGulia, , 2018b. In these studies, sleep restriction during preg- These investigators have already reported that REM and total sleep loss during late pregnancy lead the offspring to display distinct phenotypic traits of depression and hyperactivity, respectively (Gulia, Patel, & Kumar, 2015;Gulia et al, 2014;Radhakrishnan et al, 2015).…”
Section: Sleep Restriction During Pregnancy and Maternal Behaviourmentioning
confidence: 98%
“…However, the potential effects of maternal sleep restriction during pregnancy on foetal neurodevelopment have been scarcely explored. The group of Gulia and Kumar has shed light on this relationship, by means of rodent studies evaluating the effects of experimental sleep restriction during pregnancy on the brain development of offspring (Aswathy, Kumar, & Gulia, 2018a, 2018b). In these studies, sleep restriction during pregnancy was achieved by two different methods: REM sleep (platform method, 22 hr/day) and total sleep (gentle handling, 5 hr/day) during the last third of the pregnancy (gestational days, 15–20).…”
Section: Overview Of the Main Research Fieldsmentioning
confidence: 99%
“…Sleep loss during embryogenesis is a risk factor for pregnancy loss (Calegare et al, 2010), poor fetal growth and preterm delivery (Chang et al, 2010;Okun et al, 2011;Palagini et al, 2014). Lasting negative impacts of SD during pregnancy, investigated in the developing offspring, include greater amounts of active sleep and less quiet sleep compared to controls, indicative of immature brain development (Aswathy et al, 2018), and increased ultrasonic vocalizations (Gulia et al, 2015), indicative of higher sensitivity to maternal separation. As pre-adolescents, offspring display increased risk-taking behavior (Gulia et al, 2015;Radhakrishnan et al, 2015) and deficits in hippocampal-dependent learning and memory (Zhao et al, 2014(Zhao et al, , 2015.…”
Section: Fig 5 No Change In Placenta Kynurenine Pathway (Kp) Metabolites Following Sleep Deprivation (Sd)mentioning
confidence: 99%